ગણિત, ધોરણ-ત્રીજું - (:unkn) unknown (Maharashtra State Bureau of Textbook Production & Curriculum Research, 2014)
The book is a Gujarati medium Mathematic textbook for class-3.
Mathematics, Class 3
Keywords: Gujarati; ગણિત; ધોરણ-ત્રીજું; Mathematics; Class 3; Mathematics; Gujarati; Gujarati